Influence of Depletion Width on Charge Transport and Interfacial Recombination in Extremely Thin Absorber Solar Cells. Issue 2 (4th December 2015) - Edley, Michael E.; Jones, Treavor Z.; Baxter, Jason B.
Abstract : Understanding the dynamics of charge transport and recombination and their dependence on physical and electrochemical length scales in extremely thin absorber (ETA) solar cells is vital to cell design. We used J-V characterization, transient photocurrent/photovoltage, and electrochemical impedance spectroscopy to study electron transport and interfacial recombination in ETA cells. ETA cells were composed of ZnO nanowires coated with CdSe absorbers with thicknesses of 10–40 nm, with polysulfide electrolyte. The relative size of the absorber thickness and the bias-dependent depletion width was found to be a controlling factor in both transport and recombination. In thinner absorbers near short circuit, the depletion region can extend radially into the nanowire, inhibiting interfacial recombination. However, depleting the periphery of the nanowire reduces the cross sectional area for charge transport, resulting in longer characteristic collection times. Overall, cells with thicker absorbers suffered more significant bias-dependent collection, and we conclude that slight radial penetration of the depletion region into the nanowires enhances charge collection. While depletion width is often associated with charge separation in the absorber, this work highlights the importance of considering the impact of depletion width on charge transport and interfacial recombination in the design of liquid junction, semiconductor-sensitized solar cells.